The promising solar‐powered water purification based on graphene functional architectures - Yajie Hu; Houze Yao; Qihua Liao; Tengyu Lin; Huhu Cheng; Liangti Qu (EcoMat, 2022)
Abstract Solar‐powered water purification is able to gain freshwater from nonedible water by harnessing inexhaustible and pollution‐free sunlight energy, which is undergoing booming development to address the global water shortage. Due to the fascinating properties, numerous graphene‐based materials were devoted to the solar‐powered system from interfacial solar‐steam generation, towards solar pollutants degradation and even atmospheric water harvesting. Therefore, manipulations on graphene including chemical regulation and structural engineering were first introduced in this review, followed by the recent advancements in three main aspects of graphene‐based solar‐powered water purification concerning rapid steam generation, efficient pollutants degradation and significant atmospheric water harvesting. And the relationships between the designs of the materials with water purification performances were discussed in detail. Finally, a summary of challenges as well as the corresponding possible solutions were also suggested, aiming to provide scientific and technical inspirations to the flourishing solar‐powered water purification based on graphene functional architectures